Strategies of adaptation and injury exhibited by plants under a variety of external conditions: a short review - Krishania, Suman; Dwivedi, Pratibha; Agarwal, kalpana (Comunicata Scientiae, 2013)
A wide variety of favorable or disadvantageous external conditions affect the growth, developmentand productivity of plants. Plants cannot avoid adverse environmental conditions (such as soil salinity,drought, heat, cold, flooding, heavy metal contamination, predators and pathogen infections) dueto their sessile nature. Nature’s wrath in the form of various biotic and abiotic stress factors adverselyaffect plant growth and productivity causing the loss of crop yield. These abiotic and biotic stressfactors are a threat for plants, prevent them from reaching their full genetic potential and limit cropproductivity worldwide. Stress cause injury, disease or aberrant physiology by imposing a constraintor highly unpredictable fluctuations on regular metabolic patterns of plants. These fluctuations aremainly associated with altered metabolic functions; one of those is either loss of or reduced synthesisof photosynthetic pigments. This results in declined light harvesting and generation of reducingpowers, which are a source of energy for dark reactions of photosynthesis. Thus, this review articledescribes some induced changes in morphological, physiological and pigments composition incrops due to stresses and research progress in plant responses to abiotic stresses and biotic stressesis summarized from the physiological level to the molecular level. Estratégias de adaptação e injúrias demonstradas por plantas sob diferentescondições ambientais: uma curta revisão Uma grande variedade de condições externas favoráveis ou desfavorável afeta o crescimento,desenvolvimento e produtividade das plantas. Plantas não podem evitar condições ambientaisadversas (como a salinidade do solo, seca, calor, frio, cheias, infecções de contaminação,predadores e patógenos de heavy metal) devido à sua natureza séssil. Ira da natureza sob a formade vários fatores de estresse biótico e abiótico afectar negativamente o crescimento das plantase produtividade, causando a perda de rendimento da colheita. Esses fatores de estresse abióticose bióticos são uma ameaça para as plantas, impedi-los de alcançar seu potencial genéticocompleto e produtividade de culturas de limite em todo o mundo. Estresse causa lesão, doençaou fisiologia aberrante, impondo uma restrição ou imprevisíveis flutuações em padrões regularesde metabólicas de plantas. Estas flutuações são principalmente relacionadas com as funçõesmetabólicas alteradas; um desses é a perda de ou reduzida síntese de pigmentos fotossintéticos. Issoresulta na colheita de luz será recusada e Générati. Portanto, essa revisão descreve modificaçõesmorfológicas, fisiológicas e de composição de pigmentos em culturas causados por estresses e osprogressos da pesquisa quanto a resposta das plantas aos estresses abióticos e bióticos, sumarizadosem nível fisiológico e molecular.